CARDIOVASCULAR MORTALITY AND MORBIDITIES BY SYSTOLIC BLOOD PRESSURE LEVELS IN HYPERTENSIVE PATIENTS: RESULTS FROM SAMPLE COHORT OF NATIONAL HEALTH INSURANCE SERVICE. (June 2018) - Park, H.Y.; Cho, M.; Lim, N.
Abstract : Objective: Objective - We evaluated whether the achieved levels of systolic blood pressure (SBP) in treated hypertensive patients affect the cardiovascular disease (CVD) mortality and morbidities using the National Sample Cohort for 2002–2013 from a database of the National Health Insurance Service (NHIS). Design and method: Methods - The primary endpoints of the study were the incidence rate of CVD outcomes including CVD and all-cause mortality, ischemic heart disease, stroke, and heart failure. We divided hypertensive patients to three groups according to exclusive levels of SBP achieved (SBP >  = 140 mm Hg, 120–139 mm Hg, and < 120 mm Hg). Total 28, 684 hypertensive patients aged 30 to 79 treated with hypertensive agents without type 2 diabetes were analyzed (mean age, 58.2 year, men 47.9%). We calculated the incidence rate of each primary endpoint according to SBP levels and hazard ratios (HRs) by Cox multiple regression to compare between groups. Results: Results – The mean follow-up duration was 9.9 years. During the follow-up, CVD death and event occurred in 620 (2.5%) and 15, 290 (61.9%), respectively. The incidence rates (events per 1, 000 person-year) of CV events were 94.2, 110.0, and 116.0 for SBP < 120 mm Hg, 120–139 mm Hg, and >  = 140 mm Hg, respectively. The mortality rate was increased in subjects with SBP > 140 mmHg. Compared to intensive control (SBP < 120 mm Hg), hazard ratios for incident CVD for those with 120–139 mm Hg and >  = 140 mm Hg were 1.08 (P = 0.004) and 1.05 (P = 0.039) after adjusting for age, sex, obesity, current smoking status, and heavy drinking, respectively. Furthermore, CVD mortality for SBP >  = 140 mm Hg was higher than SBP < 120 mm Hg (HR = 1.30; 95% CI, 1.01–1.67). Conclusions: Conclusion - Our study shows that intensive control of blood pressure would efficiently reduce the rate of CVD events than target of 120–139 mm Hg. Beneficial effect of intensive BP control should be confirmed in prospect outcome study or clinical trial with cost-effectiveness. Figure. No caption available. Figure. Kaplan-Meir survival probability for incident of CVD according to blood pressure level